Implementation of Public Policy Regarding the Collection of Regional Taxes and Levies at the Sinjai Regency Regional Revenue Agency - Syamsiah Hasyim; Sri Rahayu Juniati; Ilham Noor; Khairul Insan (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
The aim of this research is to determine the implementation of public policies related to the collection of regional taxes and levies at the Sinjai Regency Regional Revenue Agency. This research uses a qualitative descriptive method which is intended to provide a clear overall picture and description of the existing problems in the implementation of public policies related to the collection of regional taxes and levies at the Sinjai Regency Regional Revenue Agency. The data sources used in this research are primary and secondary data sources with a total of 3 (three) informants. Data collection uses observation, interviews and documentation methods. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. From the research results, it can be concluded that people are not taxpayers due to the lack of government outreach to the community about the obligation to pay taxes, the lack of public knowledge about taxpayers.